The Impact of Perceived Organizational Support on Innovative Work Behaviour Through Psychological Empowerment: Focusing on the Moderated Mediating Role of Organizational Procedural Justice - Park, Jiwon; Kim, Woocheol (Journal of Technical Education and Training, 2022)
Although much research demonstrates that perceived organizational support (POS) enhances employee innovation (IWB), it is worth pointing out that relatively little attention has been assigned to the roles of employees’ psychological empowerment and organizational procedural justice that underlie the association between perceived organizational support and innovative behaviors. To answer this question, we hypothesized psychological empowerment as a possible mediator in the relationship between POS and IWB and organizational procedural justice as a possible moderator that influences the indirect effect of POS on IWB through psychological empowerment based on the review of the literature. The data collected from 350 employees working in Korean organizations were employed in the latent moderated structural equation (LMS) analysis. The results suggest that POS was directly correlated to psychological empowerment. Moreover, POS was not directly correlated to IBW, but it indirectly influenced IBW through psychological empowerment. The results also suggest the moderated mediating effect of organizational procedural justice in the impact of POS on IWB through psychological empowerment. Based on these findings, it would seem that creating positive organizational climates valuing contributions of individuals and caring about their well-being is important in organizations. In addition, making an effort for the provision of procedural justice, including creating transparent organizational culture, can inspire and enhance employee’s IWB.